2021
DOI: 10.3991/ijim.v15i11.18537
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Integrating an Educational Robot with Hypermedia on Students’ Acquisition of Scientific Concepts: The Case of Fifth-Grade Students

Abstract: <p class="0abstract">This study was designed to reveal the effectiveness of integrating educational robots (ERs) with hypermedia in improving the acquisition of scientific concepts among fifth-grade students in Jordan. The present study utilized a pretest-posttest quasi-experimental design with a control group (CG) and an experimental group (EG). The participants of this study consisted of 50 fifth-grade female students attending a private school in the city of Amman during the 2019/2020 academic year. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
0
5
0
2
Order By: Relevance
“…In Turkey, [71] found that robotic education can help high school students with their science performance and enhance students' relationships. In Jordan, [72] found that integrating hypermedia with robots enhances the acquisition of physical concepts among primary students.…”
Section: Robots and Learning Science Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Turkey, [71] found that robotic education can help high school students with their science performance and enhance students' relationships. In Jordan, [72] found that integrating hypermedia with robots enhances the acquisition of physical concepts among primary students.…”
Section: Robots and Learning Science Subjectsmentioning
confidence: 99%
“…It was reviewed and approved by an expert as it was implemented on a pilot sample. It's effective in acquiring scientific concepts [72]. Each robotic activity contains worksheets, manuals, and reflection tasks.…”
Section: Hypermedia and Learning Science Subjectsmentioning
confidence: 99%
“…Para Pendidikan secara massif beradaptasi dengan penggunaan teknologi digital dan elektronik dalam proses pembelajaran terutama penggunaan web, media sosial, vlog, serta platform lainnya (Furht, 2006;Klaˇsnja-Milicevi & Ivanovi, 2021). Sektor pendidikan telah mampu beradaptasi mengarah kepada kemajuan dalam penggunaan multimedia, hypermedia, dan robot pendidikan (ER) di beberapa disiplin ilmu (Ajlouni, & Jaradat, 2021).…”
Section: Pendahuluanunclassified
“…Hypermedia merupakan campuran teknologi hypertext dan multimedia yang menyediakan representasi materi pembelajaran yang berbeda dengan navigasi nonlinier. Para peneliti telah menemukan dampak positif pada proses belajar dan mengajar; terbukti dapat meningkatkan kemampuan siswa pemahaman, pemecahan masalah dan keterampilan pemrosesan ilmiah, dan kinerja akademik (Ajlouni & Jaradat, 2021;Ajlouni & Jaradat, 2020;Aksit & Wiebe, 2020;Amin & Swandi, 2017;Abanikannda, 2016;Abanikannda, 2019).…”
Section: Pendahuluanunclassified
“…Students still find it difficult to understand physics concepts because they consider physics as a subject to memorize formulas. Physical events can actually be described visually, but there needs to be a special method that is expected to be able to explain these events so that they can be understood (Ajlouni & Jaradat, 2021;Rahmawati, Rustaman, Hamidah & Rusdiana, 2018). Students are required to read physics books without being equipped with supporting multimedia (Manurung & Panggabean, 2020;Sadaghiani, 2014).…”
Section: Introductionmentioning
confidence: 99%